Reevaluating age restrictions of spinal metastasis surgery in elderly groups with over 2-year follow-up - Lenga, Pavlina; Dao Trong, Huy Philip; Papakonstantinou, Vassilios; Kiening, Karl; Unterberg, Andreas; Ishak, Basem (Neurosurgical review, 2023)
This study aimed to compare and assess clinical outcomes of spinal metastasis with epidural spinal cord compression (MESCC) in patients aged 65-79 years and >= 80 years with an acute onset of neurological illness who underwent laminectomy. A second goal was to determine morbidity rates and potential risk factors for mortality. This retrospective review of electronic medical records at a single institution was conducted between September 2005 and December 2020. Data on patient demographics, surgical characteristics, complications, hospital clinical course, and 90-day mortality were also collected. Comorbidities were assessed using the age-adjusted Charlson comorbidity index (CCI). A total of 99 patients with an overall mean age of 76.2 +/- 3.4 years diagnosed with MESCC within a 16-year period, of which 65 patients aged 65-79 years and 34 patients aged 80 years and older were enrolled in the study. Patients aged 80 and over had higher age-adjusted CCI (9.2 +/- 2.1) compared to those aged 65-79 (5.1 +/- 1.6; p < 0.001). Prostate cancer was the primary cause of spinal metastasis. Significant neurological and functional decline was more pronounced in the older group, evidenced by Karnofsky Performance Index (KPI) scores (80+ years: 47.8% +/- 19.5; 65-79 years: 69.0% +/- 23.9; p < 0.001). Despite requiring shorter decompression duration (148.8 +/- 62.5 min vs. 199.4 +/- 78.9 min; p = 0.004), the older group had more spinal levels needing decompression. Median survival time was 14.1 +/- 4.3 months. Mortality risk factors included deteriorating functional status and comorbidities, but not motor weakness, surgical duration, extension of surgery, hospital or ICU stay, or complications. Overcoming age barriers in elderly surgical treatment in MSCC patients can reduce procedural delays and has the potential to significantly improve patient functionality. It emphasizes that age should not be a deterrent for spine surgery when medically necessary, although older MESCC patients may have reduced survival.
Gesehen am 22.02.2024